You are on page 1of 9

# Matrix Exponential. Fundamental Matrix Solution. Objective: Solve dx = Ax dt with an n n constant coecient matrix A.

## x1 (t) . Here, the unknown is the vector function x(t) = . . . xn (t)

General Solution Formula in Matrix Exponential Form: C1 . x(t) = etA C = etA . , . Cn where C1 , , Cn are arbitrary constants. The solution of the initial value problem dx = Ax, dt is given by x(t) = e(tt0 )A x0 . Denition (Matrix Exponential): For a square matrix A,

x(t0 ) = x0

tA

=
k=0

t2 2 t3 3 tk k A = I + tA + A + A + . k! 2! 3!

Evaluation of Matrix Exponential in the Diagonalizable Case: Suppose that A is diago 1 .. nalizable; that is, there are an invertible matrix P and a diagonal matrix D = . n such that A = P DP
1

## . In this case, we have

etA = P etD P 1 = P 6 3 2 EXAMPLE 1. Let A = 4 1 2 . 13 9 3 tA (a) Evaluate e . dx (b) Find the general solutions of = Ax. dt dx = Ax, (c) Solve the initial value probelm dt

e 1 t

..

. e n t

P 1 .

Solution: The given matrix A is diagonalized: A = P DP 1 1 1 1 1/2 0 1 2 1/2 , D= P = 0 1 1 1 Part (a): We have

2 x(0) = 1 . 4

with 0 0 2 0 . 0 1

etA = P etD P 1 t 1 1 1/2 e 0 0 5 3 1 = 1 2 1/2 0 e2t 0 1 1 0 t 1 1 1 0 0 e 6 4 2 5et e2t 3et 3et e2t 2et et + et = 5et + 2e2t + 3et 3et + 2e2t + 2et et et . 5et + e2t 6et 3et + e2t 4et et + 2et Part (b): The general solutions to the given system are C1 tA x(t) = e C2 , C3 where C1 , C2 , C3 are free parameters. Part (c): The solution to the initial value problem is 2 11et + e2t + 8et x(t) = etA 1 = 11et 2e2t 8et . 4 11et e2t + 16et 2

Evaluation of Matrix Exponential Using Fundamental Matrix: In the case A is not diagonalizable, one approach to obtain matrix exponential is to use Jordan forms. Here, we use another approach. We have already learned how to solve the initial value problem dx = Ax, dt x(0) = x0 .

We shall compare the solution formula with x(t) = etA x0 to gure out what etA is. We know the general solutions of dx/dt = Ax are of the following structure: x(t) = C1 x1 (t) + + Cn xn (t), where x1 (t), , xn (t) are n linearly independent particular solutions. The formula can be rewritten as C1 . x(t) = [ x1 (t) xn (t) ] C with C = . . . Cn For the initial value problem, C is determined by the initial condition [ x1 (0) xn (0) ] C = x0 = C = [ x1 (0) xn (0) ]1 x0 .

Thus, the solution of the initial value problem is given by x(t) = [ x1 (t) xn (t) ] [ x1 (0) xn (0) ]1 x0 . Comparing this with x(t) = etA x0 , we obtain etA = [ x1 (t) xn (t) ] [ x1 (0) xn (0) ]1 . In this method of evaluating etA , the matrix M (t) = [ x1 (t) xn (t) ] plays an essential role. Indeed, etA = M (t)M (0)1 . Denition (Fundamental Matrix Solution): If x1 (t), , xn (t) are n linearly independent solutions of the n dimensional homogeneous linear system dx/dt = Ax, we call M (t) = [ x1 (t) xn (t) ] a fundamental matrix solution of the system. (Remark 1: The matrix function M (t) satises the equation M (t) = AM (t). Moreover, M (t) is an invertible matrix for every t. These two properties characterize fundamental matrix solutions.) (Remark 2: Given a linear system, fundamental matrix solutions are not unique. However, when we make any choice of a fundamental matrix solution M (t) and compute M (t)M (0)1 , we always get the same result.)

## EXAMPLE 2. Evaluate etA

Solution: We rst solve dx/dt = Ax. We obtain 3 1 1 t + C2 e2t 1 + C3 e2t 0 . x(t) = C1 e 1 1 0 1 This gives a fundamental matrix solution: The matrix exponential is etA = M (t)M (0)1 3et 2e2t = et + 2e2t et e2t EXAMPLE 3. Evaluate e
tA

7 9 9 for A = 3 5 3 . 3 3 5

e2t e2t 0

e2t 0 . e2t

e2t e2t 0

## 3et 3e2t et + 2e2t et e2t

Solution: We rst solve dx/dt = Ax. We obtain 1 2t 2 3 x(t) = C1 et 1 + C2 e3t 1 + C3 e3t 1/2 + t . t 1 1 This gives a fundamental matrix solution: t 3e 2e3t e3t M (t) = et et e3t The matrix exponential is etA = M (t)M (0)1 3et = et et 2e3t e3t e3t 1 3 2 1 e3t 2te3t 1 3t e + te3t 1 1 1/2 2 1 1 0 te3t 6et 6e3t 20te3t 4te3t 2et + 3e3t + 10te3t 2te3t . 2et 2e3t + 10te3t e3t 2te3t 4 e3t 2te3t 1 3t e + te3t . 2 te3t

5 8 4 2 for A = 3 2 . 6 14 5

## EXAMPLE 4. Evaluate etA for A =

9 5 . 4 5

Solution 1: (Use Diagonalization) Solving det(A I) = 0, we obtain the eigenvalues of A: 1 = 7 + 4i, 2 = 7 4i. Eigenvectors for 1 = 7 + 4i: are obtained by solving [A (7 + 4i)I]v = 0: v = v2
1 2

+i . 1

()

Eigenvectors for 2 = 7 4i: are complex conjugate of the vectors in (). The matrix A is now diagonalized: A = P DP 1 with P = We have etA = P etD P 1 1 1 1 1 +i i e(7+4i)t 0 + 1i 2i 2 2 4 = 2 1 1 (74i)t i 1i 1 1 0 e 2 2 4 1 1 (7+4i)t 1 1 5 (7+4i)t 5 (74i)t ( 2 4 i)e + ( 2 + 4 i)e ie 8 ie(74i)t 8 . = 1 (74i)t 1 1 1 1 1 (7+4i)t (7+4i)t (74i)t + 2 ie ( 2 + 4 i)e + ( 2 4 i)e 2 ie Solution 2: (Use fundamental solutions and complex exp functions) A fundamental matrix solution can be obtained from the eigenvalues and eigenvectors: M (t) = The matrix exponential is e
tA 1 ( 2 + i)e(7+4i)t e(7+4i)t 1 ( 2 i)e(74i)t . e(74i)t 1 2

+i 1

1 2

i , 1

D=

7 + 4i 0

0 . 7 4i

## = M (t)M (0) 1 1 (7+4i)t 1 + ( 2 + 1 i)e(74i)t ( 2 4 i)e 4 = 1 1 ie(7+4i)t + 2 ie(74i)t 2

( 1 + i)e(7+4i)t = 2 (7+4i)t e

1 ( 2 i)e(74i)t e(74i)t

1 2

+i 1

1 2

i 1

5 (7+4i)t ie 8

5 8 ie(74i)t

(1 2

1 i)e(7+4i)t 4

1 (2

1 i)e(74i)t 4

Solution 3: (Use fundamental solutions and avoid complex exp functions) A fundamental matrix solution can be obtained from the eigenvalues and eigenvectors: M (t) = e7t
1 2

1 2

7t

1 2

1 0

## 5 4 e7t sin 4t . 1 e cos 4t 2 e7t sin 4t

APPENDIX: Common Mistakes Since the years of freshmen calculus, we all loved the exponential function ex with scalar variable x. There are tons of simple and beautiful formulas for the scalar function ex . The matrix exponential is, however, a quite dierent beast. We need to be a little careful in handling it. Here are some common mistakes I have seen people make: et(A+B) = etA etB . The solutions of dx = A(t)x are x(t) = etA(t) C. dt Rt dx = A(t)x are x(t) = e 0 A(s)ds C. The solutions of dt = B (t)eB(t) .

eB(t)

All the above four statements are WRONG! (1) It is true that et(A+B) = etA etB if AB = BA. But in general, et(A+B) = etA etB . Example: For A= we have etA etB = but et(A+B) = (2) We learned how to solve dx = Ax dt where A is a constant matrix. 1 1 + e2t 2 1 e2t 1 e2t 1 + e2t et 0 1 et 1 1 1 et = 1 et + et 2 et et 2 et et , 2 et + et 1 1 1 1 0 0 ,B = ,A+B = , 1 1 0 0 1 1

0 . et

Unfortunately there is no general solution method for () In particular, x(t) = etA(t) C. does not solve (). This even fails in the scalar case. dx Example: The solutions of the scalar equation = (sin t)x is given by x(t) = e cos t C, dt but not et sin t C. 6 dx = A(t)x dt where A(t) is nonconstant.

## (3) Likewise, x(t) = e

Rt
0

A(s)ds

is also a wrong solution formula for (). This formula is only valid for scalar equations, i.e., when the space dimension is 1. Example: Consider dx 1 0 1 = x, x(0) = 2t 1 0 dt The solution of this initial value problem is x(t) = The function exp
0

where A(t) =

1 0 . 2t 1

et (t
t 1 t )e 2

+ 1 et 2 1 0

A(s)ds

## does not give the solution. Indeed,

t

exp
0

A(s)ds

1 = exp 0 =
1 t te 2

t t2

0 t

1 0 0 et 1 = 0
1 t te 2

et 1 tet 2

et . 1 tet 2

(4) We do have: (eb(t) ) = b (t)eb(t) holds for scalar functions b(t), and (etA ) = AetA = etA A for constant matrices A. But, in general, for nonconstant matrix function B(t), (eB(t) ) is neither B (t)eB(t) nor eB(t) B (t). Example: Let B(t) = eB(t) = t t2 0 . We have eB(t) = t et + t1 et 2 0 , et 0 et = et 3 t 1 te + 2 tet 2
1 t te 2

et 1 t 1 te 2 tet 2

0 , and hence et

t+1 t e 2

## B (t)eB(t) = eB(t) B (t) =

1 0 2t 1
1 t te 2

et 1 t te 1 tet 2 2 0 et

0 , et 0 . et

et 1 2 tet

1 0 = 2t 1

et 3 + 2 tet

All three matrix functions (eB(t) ) , B (t)eB(t) and eB(t) B (t) are dierent from each other.

##  Evaluate etA

1 1 0 for A = 2 3 2 . 0 2 1

## See next page for answers 8

 etA

1 e e2t 2 2 = 1 4t 1 2t e e 2 2
4t

3 e4t + 2 1 4t e + 2

3 2t e 2 3 2t e 2

## 5 5e2t 42te2t = e2t 21te2t 1

3et 2e2t 5et + 6e2t e3t 3et 4e2t + e3t 5et + 9e2t 3e3t 3et 6e2t + 3e3t  etA = 3et 3e2t t 2t t 2t 3t 3e 3e 5e + 9e 4e 3et 6e2t + 4e3t t 3e 2et 2et 2et et + et 4et + 5et 2et 2et  etA = 6et + 6et 6et + 6et 4et + 4et 2et et 3et 2et + 4tet 2et 2et + 3tet et + et tet 4et + 5et 3tet 2et 2et + tet  (a) etA = 6et + 6et 4tet t t t t t t 6e + 6e + 4te 4e + 4e + 3te 2et et tet 4et 3et + 6tet 1 (b) x(t) = etA 1 = 8et + 9et 6tet 8et + 9et + 6tet 1  etA = e3t cos 2t + sin 2t sin 2t 2 sin 2t , cos 2t sin 2t

or, equivalently, 1 (1 i)e(3+2i)t + (1 + i)e(32i)t 2ie(3+2i)t 2ie(32i)t etA = (3+2i)t (32i)t ie + ie (1 + i)e(3+2i)t + (1 i)e(32i)t 2 2e3t + 3 cos t + sin t 2e3t + 2 cos t sin t e3t cos t + 3 sin t 1  etA = 4e3t + 4 cos t 2 sin t 4e3t + cos t 3 sin t 2e3t + 2 cos t + 4 sin t 5 2e3t + 2 cos t 6 sin t 2e3t 2 cos t 4 sin t e3t + 6 cos t + 2 sin t